2021
DOI: 10.2478/revecp-2021-0004
|View full text |Cite
|
Sign up to set email alerts
|

Transport in times of an epidemic: public transport measures in the Czech Republic and its regions

Abstract: In the first half of 2020, the global pandemic of the COVID-19 virus became a phenomenon affecting all spheres of human life. Measures against the spread of the virus have led to restrictions in life in public spaces and have also affected the transport sector. These impacts consisted of two types - firstly, the number of connections was reduced due to a drop in transport demand, and secondly, it was necessary to comply with hygiene measures on the part of carriers and passengers. The impacts of these measures… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 19 publications
0
3
0
1
Order By: Relevance
“…Bus services were cancelled more frequently than rail services for various reasons. These reasons are explained in more detail by Vrána et al (2021). Most importantly there is an ambivalence between private and public transport companies.…”
Section: Discussion Of Survey Findings In Context Of Pandemicmentioning
confidence: 99%
See 2 more Smart Citations
“…Bus services were cancelled more frequently than rail services for various reasons. These reasons are explained in more detail by Vrána et al (2021). Most importantly there is an ambivalence between private and public transport companies.…”
Section: Discussion Of Survey Findings In Context Of Pandemicmentioning
confidence: 99%
“…The Centres for Disease Control and Prevention guidelines recommend certain behaviours when using public transportation, such as hand hygiene, avoiding touching surfaces, and social (physical) distancing (CDC, 2020). Vrána et al (2021) identified 30 measures taken on public transportation in the Czech Republic. Some of the measures were related to physical prevention of virus spread (e.g.…”
Section: Covid-19 In the Czech Republicmentioning
confidence: 99%
See 1 more Smart Citation
“…Con respecto a la frecuencia de viajes y su relación con el transporte público observamos que en la gran mayoría de los estudios tiene una gran representatividad y se presentó de manera general a nivel mundial, teniendo diversas causas, como la que encontramos en el estudio realizado en república checa por Vrana et al (2021) donde la principal razón en la reducción de la demanda del transporte público fue que el usuario prefirió el trabajo desde casa, la enseñanza presencial fue abolido, los servicios eran limitados y se animaba a los ciudadanos a no salir a menos que absolutamente necesario, la reducción de la demanda también podría estar relacionada con el miedo a infección, ya que el transporte público es utilizado por más personas que el transporte individual y es más arriesgado, mientras en Lahore, Pakistán el estudio de Abdullah M,. et al (2021).…”
Section: Metodologiaunclassified